Integrating Career Orientation into High School Education: Preparing Students for Lifelong Success - Hangivola Emyblonde Ratna; Muhammad Akbar; Muliadi Mau; Ralaivao Hanginiaina Emynorane (Mitra Edukasi dan Publikasi, 2026)
Integrating career orientation into high school education is a critical step in equipping students to make informed and purposeful decisions about their future. Considering the growing diversity of career opportunities and the increasing competitiveness of the global labor market, such programs play a key role in helping students understand professional pathways and the competencies required for success. This study investigates the benefits and impact of structured career orientation initiatives on students' decision-making processes at the high school level. Using documentation analysis, the study examined 32 documents consisting of research reports, educational policy documents, journal articles, school activity records, and relevant theoretical sources that met specific criteria of relevance, recency, and completeness. The analysis followed three stages, namely data reduction, categorization, and conclusion verification, allowing for a systematic interpretation of how career orientation programs function in various educational settings. The findings indicate that career orientation not only introduces students to diverse fields of work but also enables them to recognize their individual interests, talents, and necessary skills to achieve long-term goals. Additionally, the program strengthens students' confidence in selecting appropriate career paths and emphasizes the collaborative role of parents and teachers in offering consistent guidance and support. These findings also contribute to the achievement of SDG 4 through inclusive quality education, SDG 8 by supporting students’ readiness for decent work, SDG 10 by reducing disparities in educational and career access, and SDG 17 through strengthened collaboration among schools, families, and stakeholders.